Sustainable human health: practical innovations of “Holding Groups for Mutual Support” (HGMS) in active aging - Zhihong Zeng; Zhihong Zeng; Chaoran Wang; Shengnan Wu; Shengnan Wu (Frontiers in Public Health)
In a rapidly aging global society, “sustainable human health” and “active aging” have become significant international concerns. The growing demand for high-quality older adult care, alongside resource disparities, challenges sustainable active aging strategies. As the nation with the largest older adult population, China faces the urgent need to establish a sustainable older adult care system that enhances the health and well-being of older adults. “Holding Groups for Mutual Support (HGMS)” promotes autonomous aging choices and emphasizes dignified living through “home, gathering, mutual support, and self-care,” addressing key issues like resource imbalances and inadequate policies. This study utilizes a mixed-methods approach that integrates both qualitative and quantitative techniques to systematically investigate the perspectives of 17 members aged 60 to 80 from the HGMS, alongside insights from 146 key stakeholders, which include family members, government representatives, enterprises, and mass media. This research identifies stakeholder attitudes toward the HGMS model, analyzes its challenges in the current social context, and explores its potential impacts on sustainable older adult care. Findings indicate that the HGMS model improves resource sharing and environmental protection while addressing the supply-demand imbalance in traditional older adult care. However, challenges remain, including inadequate policy backing, cognitive biases, and uneven resource allocation. This study provides valuable insights for developing sustainable older adult care systems in China and globally.